2023
DOI: 10.1186/s10020-022-00586-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors: key regulatory targets of vascular smooth muscle cell in atherosclerosis

Abstract: Atherosclerosis (AS), leading to gradual occlusion of the arterial lumen, refers to the accumulation of lipids and inflammatory debris in the arterial wall. Despite therapeutic advances over past decades including intervention or surgery, atherosclerosis is still the most common cause of cardiovascular diseases and the main mechanism of death and disability worldwide. Vascular smooth muscle cells (VSMCs) play an imperative role in the occurrence of atherosclerosis and throughout the whole stages. In the past, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 165 publications
0
4
0
Order By: Relevance
“…In endothelial cells, KLF5 has been shown to play a pathogenic role in the development of atherosclerosis [ 50 , 51 ]. KLF5 plays an important role in the proliferation of vascular smooth muscle cells (VSMCs) and is induced in response to vascular injury.…”
Section: The Biological Function Of Kruppel-like Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In endothelial cells, KLF5 has been shown to play a pathogenic role in the development of atherosclerosis [ 50 , 51 ]. KLF5 plays an important role in the proliferation of vascular smooth muscle cells (VSMCs) and is induced in response to vascular injury.…”
Section: The Biological Function Of Kruppel-like Factorsmentioning
confidence: 99%
“…Activation of the PI3K/Akt and MAPK pathways leads to increased KLF5 gene expression in VSMCs. KLF5 mRNA levels increase rapidly in neointimal VSMCs after vascular injury [ 50 , 68 , 69 ].…”
Section: The Biological Function Of Kruppel-like Factorsmentioning
confidence: 99%
“…The present Research Topic, entitled "Transcription Factors and Arrhythmogenesis" aims at highlighting the functional role of gene regulatory networks of cardiac enriched transcription factors and their target genes in the pathophysiology of cardiac arrhythmias. Generally speaking, transcription factors bind to the promoter regions of target genes and regulate their expression (Ciccarelli et al, 2011;Larsen et al, 2020;Henley and Koehler, 2021;Tang et al, 2021;de Mattos et al, 2022;Xiao et al, 2022;Jiang and Qian, 2023;Yu et al, 2023;Zhao et al, 2023). Transcription factors can regulate arrhythmogenesis by modulating the expression of genes involved in the cardiac conduction system and/or myocardial structures, as well as through indirect effects on ionic currents, calcium homeostasis, inflammation, oxidative stress, and cardiac remodeling (Liang et al, 2015;Lu et al, 2015;Crespo-Garcia et al, 2022).…”
Section: Editorial On the Research Topic Transcription Factors And Ar...mentioning
confidence: 99%
“…Additionally, H 2 S has been shown to inhibit VSMC calcification by suppressing the Wnt/beta-catenin pathway [95]. Studies have demonstrated that H 2 S can regulate cell proliferation in VSMCs by inhibiting cell cycle progression and inducing cell cycle arrest by downregulating the expression of cyclin D1 and CDK4, critical regulators of the G1 phase [96]. Additionally, H 2 S has been shown to induce apoptosis in VSMCs by activating the caspase-dependent apoptotic pathway [97].…”
Section: Main Outlines Limitations and Future Directionsmentioning
confidence: 99%